Impacto del teletrabajo en la dirección y comunicación de las organizaciones del sector TIC - Roca Pulido, Juan Carlos; Martínez López, Francisco José; Ríos Martín, Miguel Ángel (Cuadernos de Estudios Empresariales, 2006)
In this article we are going to deepen in the analysis of the existing associations between the different modalities from telecommuting in the sector of CIT and variables related to the direction and communication patterns. On the one hand, we will abound in the form at that controls the results of telecommuters, the moment in which the control is made and, in this point, if they are the same that they are applied to non-telecommuters. Also, we will try to know the differences with respect to the opinion of if the supervision of telecommuters requires more time than the one of colleagues and the degree of autonomy of them to make decisions. On the other hand, we will emphasize the possible differences found with respect to the influence that has telecommuting on some of the communication variables and the opinions related to the effectiveness of the communications with the teleworkers, characteristics of the remote direction or the way to understand the work of the supervisor.